The Controversy Persists: Is There a Qualification Criterion to Utilize Inhaled Nitric Oxide in Pre-term Newborns? - Vieira, Frederico; Makoni, Marjorie; Szyld, Edgardo; Sekar, Krishnamurthy (Frontiers in Pediatrics, 2021)
Inhaled nitric oxide (iNO) use in premature newborns remains controversial among clinicians. In 2014, the American Academy of Pediatrics, Committee on Fetus and Newborn released a statement that the available data do not support routine iNO use in preterm newborns. Despite the absence of significant benefits, 2016 California data showed that clinicians continue to utilize iNO in preterm infants. With studies as recent as January 2017, the Cochrane review confirmed no major advantages of iNO in preterm newborns. Still, it recognized that a subset of preterm infants with pulmonary hypertension (PHTN) had not been separately investigated. Furthermore, recent non-randomized controlled trials have suggested that iNO may benefit specific subgroups of preterm newborns, especially those with PHTN, prolonged rupture of membranes, and antenatal steroid exposure. Those preterm infants who showed a clinical response to iNO had increased survival without disability. These findings underscore the need for future studies in preterm newborns with hypoxemic respiratory failure and PHTN. This review will discuss the rationale for using iNO, controversies regarding the diagnosis of PHTN, and additional novel approaches of iNO treatment in perinatal asphyxia and neonatal resuscitation in the preterm population less than 34 weeks gestation.